Hume: the power of abduction and simple observation in economics - Jorge M. Streb (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2010)
In Hume's epistemology, induction leads to discovery in matters of fact. However, because of the poor data Hume analyzes the balance of trade with a thought experiment, doing what Mill makes explicit afterwards: reason from assumptions, to reach conclusions which are true in the abstract. Hume's potential explanation, what Peirce later calls abduction, is backed by a case study, the price revolution of the 16th century, which supports half his abductive inference, when money supply is multiplied fivefold. Given that economics reasons abductively, Hume's attention to realistic hypotheses and the adjustment process matters.
Keywords: B1; B4; E4; E5; F1; 330; abduction; case studies; realistic assumptions; Hume; Mill; Peirce; Hayek; Akerlof